Partial Purification of Cholinesterase Enzyme and Study of Some Biochemical Variables in Patients with Type 2 Diabetes, Along with Analysis of the Linear Correlation between Enzyme Levels and Clinical Variables - Hussein, Firas Abed; Maher, Dr. Firas Taher (Journal of Science in Medicine and Life, 2024)
Diabetes is a metabolic disorder characterized by high blood sugar levels. This increase occurs due to a reduction in insulin secretion or a decrease in the body's ability to use insulin effectively, leading to the accumulation of glucose in the blood. Insulin regulates blood sugar levels by facilitating the entry of glucose molecules into cells for storage or energy production[1]. Objectives The current study aimed to achieve molecular purification of the enzyme acetylcholinesterase and analyze the linear relationship between enzyme levels and clinical variables in diabetic patients while measuring the levels of C-PEP, GLP-1, R.B.S, F.B.S, Hb1Ac, Urea, and Creatinine. Materials and Methods This study included 90 samples, comprising 60 diabetic patients and 30 healthy individuals as a control group, with ages ranging from 30 to 75 years. Blood samples (3-5 ml) were collected, and serum was obtained. Necessary tests were performed on all samples. Results The results showed a significant decrease in the level of the enzyme acetylcholinesterase in diabetic patients compared to the control group (p<0.01). Additionally, there were statistically significant differences in enzyme levels between genders and age groups. The study indicated statistical significance at (p>0.05) in enzyme levels, while no significant difference was found in GLP levels at the probability level (P≤0.01). A decrease in the concentration of C-peptide hormone was also observed in diabetic patients compared to healthy individuals at the level (p>0.05). The results further indicate a significant increase in glucose concentration in diabetic patients at the probability level (P≤0.01). The statistical results also showed a highly significant increase in urea levels in diabetic patients compared to the control group, with this increase being statistically significant (p≤0.001). However, the results indicate no significant increase in creatinine levels in diabetic patients compared to the control group at the same probability level (p≤0.001). Conclusion The study concluded a decrease in the level of the enzyme acetylcholinesterase in diabetic patients compared to healthy individuals.